EVALUATION OF THE ACQUISITION AND PAYMENT CYCLE: A CASE STUDY OF PT INDOSPRING TBK AND PT GUNAWAN DIANJAYA STEEL TBK - Fera Amelia Putri; A. Nurul Fatima Zahra; Zauhar Qalbi; Dwi Yanti; Muh Alfa Reza Malik (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
This study aims to evaluate the comparison of the acquisition and payment cycles of PT Indospring Tbk and PT Gunawan Dianjaya Steel Tbk for the period 2022–2023. The method used is a quantitative approach with a comparative review, using secondary data from the financial statements of both companies. The results show that PT Indospring Tbk has an advantage in funding stability with a Debt to Asset Ratio (DAR) consistently below 25%, while PT Gunawan Dianjaya Steel Tbk has a higher DAR, although it improved from 50.24% to 42.83%. In terms of debt turnover ratio, Gunawan Dianjaya Steel recorded a significantly higher ratio of more than 40 times per year, whereas Indospring remained at a more stable range of 8–9 times in managing cash flow. These findings highlight that the effectiveness of the acquisition and payment cycles is strongly influenced by the balance between funding structure and payment policies.